Improving Representational Competence in Physics Education: A Systematic Review and Future Research Directions - Koswojo, Jane; Kusairi, Sentot; Sutopo, Sutopo; Supriana, Edi (FKIP Universitas Lampung, 2024)
Several studies have been conducted to improve students' representational competence in physics, but a comprehensive review of these efforts is lacking. This manuscript summarizes current knowledge, identifies gaps, and suggests future research directions to improve students' representational competence. A review of 26 scientific articles from 2000 to 2023 in physics education journals was conducted. The findings revealed that (a) a consistent learning approach can improve students' representation competence, (b) constructivist-based learning models show a significant impact on the understanding of various forms of representation, (c) interactive learning media, such as simulations and animations, are more effective than conventional media, and (d) media that integrate local cultural elements have the potential to increase student engagement and understanding. However, the study also found limitations in the development of media that support low-achieving students, the integration of technology into representation learning, and long-term research on the impact of learning interventions. The main implication is the need for a more integrated and technology-based approach to improve representation competence across different levels of students. As a novel contribution, this study recommends the development of Android-based applications for physics representation training, testing the effectiveness of local culture-based media, long-term impact research, and evaluation of user experience and feedback to strengthen future learning designs. Keywords: representation competence, increased representational competence, next effort, literature review.DOI: http://dx.doi.org/10.23960/jpmipa/v25i4.pp1906-1924